Identification of Immunodominant Antigens From a First-Generation Vaccine Against Cutaneous Leishmaniasis - Germanó, María José; Mackern-Oberti, Juan Pablo; Vitório, Jessica Gardone; Duarte, Mariana Costa; Pimenta, Daniel Carvalho; Sanchez, Maria Victoria; Bruna, Flavia Alejandra; Lozano, Esteban Sebastián; Fernandes, Ana Paula; Cargnelutti, Diego Esteban (Frontiers in Immunology, 2022)
Leishmaniasis is a neglected tropical disease (NTD) caused by parasites belonging to the Leishmania genus for which there is not any vaccine available for human uses. Thus, the objectives of this study were to evaluate the immunoprotective effect of a first-generation vaccine against L. amazonensis and to identify its immunodominant antigens. BALB/c mice were inoculated with PBS; total L. amazonensis antigens (TLA); or TLA with Poly (I:C) and Montanide ISA 763. The humoral and cellular immune response were evaluated before infection by measuring IgG, IgG1 and IgG2a on serum and IFN-γ, IL-4, IL-10 and cell proliferation on splenocytes culture from vaccinated mice. Immunized mice were challenged with 104 infective parasites of L. amazonensis on the footpad. After infection, the protection provided by the vaccine was analyzed measuring lesion size, splenic index and parasite load on footpad and spleen. To identify immunodominant antigens, total proteins of L. amazonensis were separated on 2D electrophoresis gel, transferred to a membrane which was incubated with serum from immunoprotected mice. The antigens recognized by serum were analyzed through a mass spectrometric assay (LC-MS/MS-IT-TOF) to identify their protein sequence, which was subjected to bioinformatic analysis. The first-generation vaccine induced higher levels of antibodies, cytokines and cell proliferation than controls after the second dose. Mice vaccinated with TLA + Poly (I:C) + Montanide ISA 763 showed less footpad swelling, splenic index and parasite load than control groups (PBS and TLA). Four immunodominant proteins were identified by mass spectrometry: cytosolic tryparedoxin peroxidase, an uncharacterized protein, a kinetoplast-associated protein-like protein, and a putative heat-shock protein DNAJ. The identified protein showed high level of conserved sequence among species belonging to the Leishmania genus and the Trypanosomatidae family. Those proteins also proved to phylogenetically divergent to human and canine proteins. TLA + Poly (I:C) + Montanide ISA 763 could be used as a first-generation vaccine against leishmaniasis. The four proteins identified from the whole-protein vaccine could be good antigen candidates to develop a new generation vaccine against leishmaniasis.